Unlocking the potential of volunteers. (10th January 2019) - Foster, Sam
Abstract : Sam Foster, Chief Nurse, Oxford University Hospitals, considers the need for an evidence base for a best practice NHS volunteer model to improve care quality, rather than using volunteers as a means to cut costs and training initiatives that could include enabling volunteers to switch careers